Pengaruh Harga, Promosi, Kualitas Produk Dan Acuan Kelompok Terhadap Pengambilan Keputusan Handphone Android ( Studi kasus pada Mahasiswa Fakultas Ekonomi dan Bisnis Unisma angkatan 2017 ) - Aziz, Yazid Nur; Widarko, Agus; Wahono, Budi (E-JRM : Elektronik Jurnal Riset Manajemen, 2024)
Abstract This research was conducted at the Faculty of Economics and Business, Islamic University of Malang. The type of research used is explanatory research with a quantitative approach. The purpose of this study was to determine the effect of price, promotion, product quality and group reference on decision making. The independent variables used are price, product quality promotion and group reference, while the dependent variable is decision making. The sample used in this study was 115 respondents who were students of the Unisma Faculty of Economics and Business class 2017. The data collection technique used a questionnaire. The analytical method used is instrument test, multiple linear regression analysis, classical assumption test, determination test, f test and t test using SPSS 16.0 computer software for data processing. The results of this study indicate that price affects decision-making, promotions affect decision-making, product quality affects group references and affects decision-making. Price, promotion, product quality and group reference simultaneously affect decision making. Keywords: Price, Promotion, Product Quality, Reference Group Decision Making.